Framing Information and its Impact on Saving Decision in Conventional and Sharia Banks: Experimental Study of Students of the Faculty of Islamic Economics and Business in Yogyakarta - Ipuk Widayanti (Global Review of Islamic Economics and Business, 2015)
Islamic and Conventional Banks in delivering information of margin in saving product have different ways.  Islamic bank uses “nisbah” while conventional bank uses interest. Both have different words and disclosure but in the nominal calculation of nisbah and interest is same, because Islamic bank uses Profit Equilization Reserve which the function is as allowance, and to simply it, Islamic banking informs that to consumer as Equivalent Rate. By using Attribute Framing and Risky Choice Framing this research aims to test the information frame of nisbah and interest and it influences on saving decision making. Quasi Experiment Model is used with 49 students of Islamic Economic Studies as subject of experimental group and 20 students of other studies except Islamic Economic as subject of control group. Experimental design of this research is between subject 2X2 by using 2 cases and Random Assignment technique. Two Way ANOVA is used as analitical tool. The result of this research is when information of margin is framed in gain domain/positive frame and loss domain/positive frame subject decision in saving is less risky while when information of margin is framed in gain domain/negative frame and loss domain/negative frame subject decision in saving is risk seeking. The largest framing effect is on the certain/probability (gain domain/positive frame) and the smallest effect is on uncertain/presentation (loss domain/negative frame).